Variable message sign (VMS) information design : From user perspective / Noor Azlina Samsudin - Samsudin, Noor Azlina (2005)
This research examines the Variable Message Sign (VMS) information design from user perspective. VMS information design will affect the user when they are using title road or highway to travel. The poor or unreadable information will make the user unable to make decision to change the route or slower the speed at certain road. Furthermore, some users are difficult to understand the messages that are displayed by VMS. Therefore, this research will give an opportunity to user to view or give their opinion about the VMS information design that are suitable for their eye view or other user in order to ensure their safety while they are commute. The research method that use in this research is consists of research model and research approach and methodology. Technology Acceptance Model (TAM) is use as a research model that represents an important theoretical contribution toward understanding of Information System (IS) usage. There are two types of research approach that had been used which are including primary data and secondary data. Questionnaire is use as primary data while journals, articles and Internet as a secondary data. The finding of this research show that majority of the respondent was satisfied with the service that provided by VMS. They also admit that VMS provides many advantages to them. The types of gender, age, level education and profession field had been identified as factors that influencing user perspective towards VMS. There are also a few recommendations on improving VMS information design based on user perspective.